Transformasi Nilai-Nilai Sejarah Peradaban Islam Pada Era Society 5.0 - Nabila Rizki Aprilia; Elsa Nandita; Nur Hidayah Limbong; Zulham Zulham (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
The existence of religion is an important part of a person's life, because it has sacred value and opens the mind to solve life's problems. Currently, diverse human personalities believe in faith and trust which is practiced every day as proof that they have a God who provides a better life and a fully realized leader for humanity. Islamic civilization is a journey towards the ability of Muslims to accept and understand their own development. Islam is a religion that has a big influence on the lives of society 5.0. The main issue is how Islam can form solutions to problems towards Islamic progress based on the level of technological development and human resource development in society in the 5.0 era. Therefore, according to this source, we can understand that Islamic civilization was formed primarily for the implementation of processes in the fields of science, society and culture as an example of the progress of Islamic society towards the teaching of the Islamic religion and its use. technology. Accepting the universal values ​​of Islamic civilization, the grace of the universe, beyond time and place, three pillars are built, namely faith, obedience and sincerity (akhlak/sufism) through technological developments in the era of Society 5.0. Therefore, in the era of modernization, it is important to revive Islamic values ​​in education. It is hoped that it will be able to give birth to a generation with commendable morals and excellence in science and technology, so that it can prepare to face the era of society 5.0. The research method uses a method (library research) by collecting several literature related to the problems and objectives of the research. Data collection on the results of previous research is used as a benchmark to support data in research on the transformation of historical values ​​of Islamic civilization during society 5.0.